1998
DOI: 10.1159/000029648
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of LINAC Stereotactic Radiosurgery on Epilepsy Associated with Arteriovenous Malformations

Abstract: Reduction of seizures associated with arteriovenous malformations (AVMs) following radiosurgery has been reported. This investigation assessed the effect of LINAC radiosurgical treatment of AVMs on the associated epilepsies correlated to AVM location, size, seizure type, and postradiosurgical thrombosis. Of 100 patients with AVMs, 33 presented with seizures (11 generalized tonic-clonic seizures, 8 simple partial seizures, and 14 complex partial seizures with or without secondary generalization). Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 21 publications
(33 reference statements)
4
29
0
1
Order By: Relevance
“…16,21,43,73 In this systematic review, we observed an overall seizure incidence of 28% in studies that included AVM patients treated with SRS. Risk factors While defining factors for seizure development in patients with AVMs may be important for risk stratification, analyzing seizure outcome following AVM treatment will help direct future therapy.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…16,21,43,73 In this systematic review, we observed an overall seizure incidence of 28% in studies that included AVM patients treated with SRS. Risk factors While defining factors for seizure development in patients with AVMs may be important for risk stratification, analyzing seizure outcome following AVM treatment will help direct future therapy.…”
Section: Discussionmentioning
confidence: 84%
“…22,37,39,57 Relationships between seizure characteristics and seizure outcomes following SRS were also inconsistent; complex partial seizures with or without secondary generalization, generalized tonic-clonic seizures, infrequent and shortduration seizures, and seizure frequency have been associated with improved seizure control. 16,33,39,57,71 In contrast, other studies have also found no significant relationship between seizure outcome and seizure type, duration, frequency, and pattern or age at seizure onset. 16,37,39,57,71 The influence of hemorrhage on seizure outcome was also controversial.…”
Section: Obliteration and Other Factors Related To Seizure Outcomementioning
confidence: 84%
See 3 more Smart Citations